Navigating COVID-19 in Asia and the Pacific - Susantono, Bambang; Sawada, Yasuyuki 1967-; Park, Cyn-Young (Asian Development Bank, 2020)
This book gathers analysis and ideas to help policy makers tackle the impacts of the coronavirus disease (COVID-19) and build a more resilient and sustainable future.